PROSPECTS OF INTRODUCING INNOVATIONS IN PERSONAL INSURANCE ON THE EXAMPLE OF FOREIGN COUNTRIES - D. Tretiak (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In order to find ways to innovate the development of personal insurance, problems were summarized and constraining factors that prevent personal insurance from developing as a separate insurance industry. These problems include: the lack of a developed insurance infrastructure, low insurance culture, unfinished reform in the field of health insurance, the slow pace of economic restructuring, low level of the population's solvency, a protracted political crisis, insecurity of insurance companies. Analysis of global trends in the development of insurance business has shown that those insurance companies that will be ready to offer their clients detailed risk analysis and innovative insurance products will win in competition. On the basis of foreign experience, innovative directions for the development of personal insurance in Ukraine were proposed. In particular, during the research, various ways of innovative improvement of life insurance, medical insurance and accident insurance were identified and proposals were developed to expand the assortment of insurance products and distribution channels for these types of insurance.